Analysis of TPACK-Based Learning for Teachers of Madrasah Tsanawiyah in Banyumas Regency, Indonesia - Abu Dharin; Agus Setiawan; Ischak Suryo Nugroho; Erma Suryani Sahabuddin; Dwi Priyanto (Nazhruna: Jurnal Pendidikan Islam, 2025)
Integrating technology, pedagogy, and content knowledge is critical for effective teaching in the 21st century, particularly in the aftermath of the COVID-19 pandemic, which has intensified the reliance on digital tools in education. This study examines the interrelationships among the six components of the Technological Pedagogical Content Knowledge (TPACK) framework as demonstrated by Madrasah Tsanawiyah teachers in Banyumas Regency, Indonesia. A quantitative research design was employed, with participants selected through proportional random sampling from the population of Madrasah Tsanawiyah teachers in the region. Data were collected using a questionnaire based on a 4-point Likert scale and analyzed through Structural Equation Modeling (SEM). The findings indicate that each component: Technological Knowledge (TK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK): exerts a positive and statistically significant influence on overall TPACK. Specifically, significant positive relationships were observed between TK and TPACK, PK and TPACK, TCK and TPACK, PCK and TPACK, and TPK and TPACK. These results underscore the necessity of reinforcing all dimensions of the TPACK framework to improve teaching effectiveness in Madrasah Tsanawiyah, with the quantitative analysis affirming the strength and significance of these associations.